Достатні умови стійкості лінійних імпульсних систем змінної структури - Двірний, О.І.; Іванов, І.Л. (Видавничий дім "Академперіодика" НАН України, 2008)
The asymptotic stability of a solution of the linear system with structural perturbation is studied. An application of the obtained results is illustrated.